Implementation of Good Hygiene Practice (GHP) In Poultry Product Industry: Sausage Commodity - Rahmawati Rahmawati; Dewi Fara Afifa; Ivan Atmaja Ghani; Azmil Umur; Btari Nur Azizah; Dian Ayuning Puspa Dewi; Alga Yean Fatika; Nash’wa Aqillah Yvonne Ramadhani; Maria Nurlian Turnip (Nusantara Science and Technology Proceedings, 2024)
Food safety is one of the requirements to ensure that a food product is produced according to standards and safe for consumption by consumers. The food industry, especially for the fresh food processing industry such as poultry products, has a higher risk of food safety. Biological, chemical, and physical hazards can appear during the production process that is supported by industrial environmental factors. This study aims to review and identify several forms of efforts to implement Good Hygiene Practices based on the production process chain by the food industry that produces sausages. The study focuses on practices that have been done by a related industry as well as things that can be of concern in the implementation of GHP. The Good Hygiene Practice (GHP) is related to hygiene and sanitation practices which are divided into nine aspects in the CAC document. Food Business Operators (FBOs) must pay attention to the implementation of GHP to ensure maximum safety of a product. Hygiene and sanitation practices relate to the environment where food products are received, stored, handled, produced or prepared until distributed. The implementation of GHP can include preventive measures to control food hazards such as designing the layout of production processes that is adapted to GHP practices, providing worker skills training, systematic cleaning, disinfection also waste management according to characteristics, personnel hygiene checks, control of production and storage temperatures, and appropriate product labeling.